2016
DOI: 10.1177/1535370216642528
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced protection against renal ischemia–reperfusion injury with combined melatonin and exendin-4 in a rodent model

Abstract: We tested the hypothesis that combined treatment with melatonin, an anti-oxidant, and exendin-4, an anti-inflammatory agent, was superior to either alone for protecting the kidney from ischemia-reperfusion (IR) injury. Male adult Sprague-Dawley rats (n¼40) were equally divided into group 1 (sham-operated control), group 2 (IR only, IR¼1h/72h), group 3 (IR-exendin-4, 10 mg/kg at 30 min, 24 h, 48 h after IR procedure), group 4 (IR-melatonin, i.p. 50 mg at 30 min, then 20 mg at 6 and 18 h after IR procedure), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…Moreover, immunofluorescent microscopic findings of CD90+/53BP1+ and CD90+/XRCC1+ cells, two indicators of deoxyribonucleic acid (DNA) damage markers, were consistent with the pattern of apoptosis (Figure I‐N). Our findings from these studies help to explain the previous results from our experimental studies . Clearly, the molecular cellular protection by melatonin treatment played a crucial role in reducing the organ damage and facilitated the recovery of the organ function from both ischemia–reperfusion and sepsis syndrome situations.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, immunofluorescent microscopic findings of CD90+/53BP1+ and CD90+/XRCC1+ cells, two indicators of deoxyribonucleic acid (DNA) damage markers, were consistent with the pattern of apoptosis (Figure I‐N). Our findings from these studies help to explain the previous results from our experimental studies . Clearly, the molecular cellular protection by melatonin treatment played a crucial role in reducing the organ damage and facilitated the recovery of the organ function from both ischemia–reperfusion and sepsis syndrome situations.…”
Section: Resultssupporting
confidence: 81%
“…Our previous experimental studies have shown that melatonin treatment significantly protects kidney, small bowel, lung, and liver, as well as urinary bladder against ischemia–reperfusion or sepsis syndrome‐induced injury or cyclophosphamide‐induced acute interstitial cystitis (Figure ). Additionally, combined melatonin–ADMSC therapy was superior to ADMSC alone for ameliorating damage of these organs …”
Section: Resultsmentioning
confidence: 98%
“…MT has been demonstrated to exert anti-inflammatory effects in the skin, intestine, and the lungs; it can also assist in relieving chronic pelvic pain in women with endometriosis (32-34). It has been shown that, acting as an anti-apoptotic and anti-oxidization agent, MT can decrease the kidney damage induced by I-R, UUO, and severe burns (35-37). It has been shown that, by suppressing nucleocytoplasmic translocation, pretreatment with MT can enhance renal regeneration in folic acid-induced AKI, thus providing further insight on the treatment of AKI (38).…”
Section: Discussionmentioning
confidence: 99%
“… 90 It has been reported that intraperitoneal injection of melatonin can reduce kidney damage induced by AKI and unilateral ureteral obstruction mainly through the antioxidant and anti-apoptotic effects. 91 92…”
Section: Hormonesmentioning
confidence: 99%